Política, gestión y evaluación de la investigación y la vinculación en América Latina y el Caribe (Ciencia abierta CLACSO, 2021)
This book brings together a set of current debates and reflections on policies and the diversity of ways in which knowledge is produced, circulated, managed and evaluated in universities in Latin America and the Caribbean. Its twenty-nine contributions written by researchers from Argentina, Bolivia, Colombia, Cuba, Ecuador, Mexico, Peru and Uruguay give an account of the challenges and reconfigurations that the functions of research, linkage and/or extension go through in dialogue with teaching, and knowledge management and research evaluation activities. The book offers a collective contribution that seeks to strengthen openness in the production and circulation of knowledge understood as a public and common good, managed by academic communities in a non-commercial manner, contextualized in Latin American universities and strengthened by a diversity of approaches.